Wybrane zagadnieniaprawnorodzinne konkubinatu - Szlęzak, Andrzej (Wydział Prawa i Administracji UAM, 1992)
The article discusses basic aspects of cohabitation without marriage in the light of family law. In Poland, the problems of cohabitation without marriage are not dealt with by family law instruments. Most issues are resolved on a civil law basis. Besides, the Supreme Court has several times held that even a mutatis mutandis application of family law provisions to cohabitees is not allowed. However, it does not mean that family law is entirely excluded from the regulation of relations arising in the marriage-like families. In particular, if the cohabiting couple has their own children, the relations between the children and their parents are regulated by means of family law provisions. It is worth stressing that in Polish law children born out of wedlock enjoy all inheritance and maintenance right towards their unmarried fathers; in turn, such fathers have full parental authority (with some exceptions) over their natural children. The other issue of importance in connection with marriagelike unions is that of the influence of cohabitation on the duty to pay alimony vested in a former spouse of one of the cohabitees. Generally, cohabitation does not lead to an automatic termination of the duty of support. However, it may be considered one of the circumstances the existence of which may lead to the modification of the duty of support, or - in some extreme cases - to the termination of such a duty. Finally, cohabitation does not have any direct influence on the duty of one of the cohabitees to pay alimony to his or her former spouse.
Cohabitation without marriage in family law